Development of plastic scintillator based primary standard for activity measurements and its performance evaluation. (December 2020) - Ravindra, Anuradha; Kulkarni, D.B.; Das, A.P.; Joseph, Leena; Sathian, V.; Dahiwale, S.S.; Dhole, Sanjay D.
Abstract: 4πβ-γ coincidence technique is a powerful tool and widely recognised method to determine the absolute activity concentration of radioactive solutions. A new plastic scintillator based coincidence system has been developed and established as a primary standard for radioactivity measurements. The performance of the system was evaluated by the standardisation of 60 Co radioactive solution due to its simple decay scheme. The activity concentration results obtained by the new system were compared with the existing proportional counter and liquid scintillation based 4πβ-γ coincidence systems. This paper discusses the design details of the new system and its performance evaluation. Highlights: A new plastic scintillator based 4pb-g has been designed, developed and evaluated. Plastic scintillator is used as beta detector and 60 Co was standardized. Performance evaluation of the new PS system and comparison with PCand LS based 4πβ-γ coincidence system. The activity concentration results obtained with new system are comparable with existing systems within uncertainty limits. Established as absolute standard for radioactivity measurements.